Co morbidity of post-traumatic-stress disorders and substance use disorder - Farmakas, Antonis; Karagiannis, George; Papastavrou, Evridiki; Kotrotsiou, Evangelia (My University, 2011)
Background: The phenomenon of substance use, abuse and dependence is a serious problem with psychological, social, physical and economic impact. The co existence of two disorders, known as co morbidity or dual diagnosis and the relationship between a psychiatric disorder and substance dependence is complicated and many scientists support that psychopathology often forms the ground for the development of dependence. The aim of the study was to explore substance use in individuals with Post Traumatic Stress Disorder (PTSD) and investigate whether the severity of PTSD is related to Substance Use Disorder (SUD) as well as the severity of drug addiction. Method and material: A cross sectional, correlational study with the use of 3 research instruments: The Treatment Demand Indicator (T.D.I.), the Addiction Severity Index (ASI) for measuring the severity of substance dependence and the Post Traumatic Stress Diagnostic Scale P.D.S. for the diagnosis of PTSD. The sample consists of 33 individuals, chosen by the members of a therapeutic program for drug dependence which combines inpatient and outpatient therapeutic interventions. The statistical analyses was performed by using the statistical program SPSS. Results: The results showed that a percentage of 40.6% of drug depended people reported symptoms of PTSD and were diagnosed with PTSD. From those, the level of impaired functioning showed that (23%) had a medium problem and the other (77%) had a serious impaired functioning level. A significant positive relationship between PTSD and severity of drug problems was found. The results showed that there was a statistically positive significant correlation between the PTSD symptom severity and the level of dependency from drugs (r=0.678, p-value=0.011). This finding shows that the higher the level of dependency, the higher the PTSD symptom severity index. Also the results showed that there was a significant correlation suggesting that those suffering from PTSD presented a bigger problem with drugs (Χ2=18.945, p-value<0.001). Therefore, those participants who had an acute problem in the level of severity of drug abuse were also suffering from PTSD (78%) and those who had a medium problem were not suffering from PTSD (90%). Conclusions: More investigation is needed to determine the relationship between the two disorders (PTSD and SUD) in order to find out which one precedes the other. In addition, it is important to investigate how one disorder affects the development of the other and how they affect, if they do, the therapeutic progress and development of the person
Keywords: Co-morbidity; Post-traumatic stress disorder; Substance use